Pictures Revisited : A Traditional Vehicle in Enhancing Young Learners’ Vocabulary - Ambigapathy, Pandian; Soubakeavathi, Rethinasamy; Lee, Bee Choo (Universiti Sains Malaysia, 2019)
The dire state of high illiteracy rate in the English language among Malaysian students speaks for the need for efficacious language learning approaches, expressly to augment learners' vocabulary knowledge which is deemed the foundation of language development. This paper overviews the various measures pictures have been traditionally utilised for successful vocabulary learning and it surmises that pictures have been gainfully employed in picture storybooks and flashcards, as well as enlarged posters and imagery creation for effective vocabulary acquisition. As aptly put by Ryan (1993, p.1), “Carefully selected pictures can be a catalyst giving rise to the production of thousands of words.” Therefore, this paper aspires to firstly, appraise the diverse ways pictures have been tapped for language development and secondly, to examine the effectiveness of the methods and pose recommendations. Leveraging on the resources and previous research findings of researchers renowned in this field as a reference, this paper focuses largely on related studies by Malaysian researchers to render it relevant to Malaysian learners. It is hoped that this review does not only furnish one with consequential insights into vocabulary development for young learners that can be applied in our Malaysian classrooms for effective teaching and learning but serves to rejuvenate interests in pictures as a means to an end where vocabulary learning is concerned. The prevailing perspective is to acknowledge the richness and scope of pictures, as well as its versatility and to capitalize on them advantageously for utmost benefits in Malaysian classrooms.